Marxismo y poder - Blanco Martín, Carlos Javier (Nómadas. Critical Journal of Social and Juridical Sciences, 2008)
We offer an approximation between Marxist Theory of Power and the Foucault´s Theory of Relational Power, far away the traditional conception of Power in terms of Political Superstructures. This essay describes Power in terms of control, submit and domination in the context of a materialistic and relational theory.